Review on the transformation of tennis development in Malaysia / Mohamad Rahizam Abdul Rahim ... [et al.] - Abdul Rahim, Mohamad Rahizam; Mohamed Shapie, Mohamad Nizam; Abdullah, Nagoor Meera; Parnabas, Vincent; Hasan, Hosni; Mohd Khir, Zulkhairi (Universiti Teknologi MARA, 2021)
This paper attempts to review the development of tennis in Malaysia and efforts made by its national governing body, Tennis Malaysia and to discuss on the development of tennis in Malaysia through the successful mode of tennis development strategy, and analyzes the successful mode of tennis development strategy in its planning and implementation. Tennis is competing with other sports in attracting the youth to take up the sport as one of their preferred leisure activities. Tennis Malaysia also engages in Junior Development activities to bring junior tennis players up the learning curve and be more competitive. Elite athlete development is the result of a combination of elite sport policies, athlete development pathways and interactions between various stakeholders that are involved in the delivery of athlete development pathways. These factors make elite athlete development a complex, multi-layered and multi-faceted field of study that necessitates specific research efforts that focus on how these factors contribute to elite athlete development in specific sports. Tennis Malaysia and its affiliates have endeavored to raise the standard of the sport in the past few years and have been relatively successful in achieving their objectives although there is much scope for improvement. The national body will continue to implement and improve its approach in developing tennis in Malaysia and will conduct some capacity building activities towards achieving excellence for tennis to continue to grow in all aspects.